Synthesis, characterization, and performance evaluation of polymeric HALS in ethylene-propylene-diene terpolymer (EPDM) - Lonkar, Sunil P.; Rana, S.; Singh, R. P.; Lacoste, Jacques; Gardette, Jean Luc; Jestin, F.; Brocord, E. (Journal of Macromolecular Science, Part A: Pure and Applied Chemistry, 2005)
A polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the maleic anhydride graft ethylene-propylene-diene terpolymer (EPDM) was synthesized. This involves photoinduced grafting of maleic anhydride groups on unsaturated sites of EPDM, followed by incorporation of amino terminated HALS. The grafting and functionalization reactions were characterized by FTIR and C-13 NMR spectroscopy. The surface changes upon degradation are studied by SEM. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The HALS grafted EPDM showed significantly improved photostabilizing efficiency.
Keywords: EPDM; light induced grafting; Photostabilization; polymeric HALS

Photooxidation of vulcanized EPDM/montmorillonite nanocomposites - Morlat-Therias, Sandrine; Fanton, Elisabeth; Tomer, Namrata S.; Rana, Sravendra; Singh, R. P.; Gardette, Jean Luc (Polymer Degradation and Stability, 2006)
The photooxidation of a vulcanized ethylene-propylene-diene monomer (EPDM)/montmorillonite nanocomposite as well as EPDM/nanocomposite with stabilizers was studied under accelerated UV-light irradiation (lambda >= 300 nm, 60 degrees C) for different times. The development of functional groups during oxidation was monitored by infrared spectroscopy. Photodegradation of the neat polymer and composites took place and the increases of absorbance in hydroxyl and carbonyl groups with irradiation times and also the decreases of the EPDM unsaturations were measured. The data indicated that the photooxidation products were not changed in the presence of the nanofiller. However, the presence of MMt was observed to dramatically enhance the rate of photooxidation of EPDM with a shortening of the oxidation induction time, leading to a decrease of the durability of the nanocomposites. On the other hand, it was observed that addition of stabilizers, either Tinuvin P or 2-mercaptobenzimidazole, was efficient in inhibiting the degradative effect of MMt. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: EPDM; Nanocomposite; photooxidation rate; stabilization

Preparation and performance evaluation of EPDM nanocomposites under accelerated weathering - Rana, Sravendra; Tevtia, Amit K.; Kumar, Bijendra; Singh, R. P. (Journal of Thermoplastic Composite Materials, 2006)
The degradability of ethylene propylene diene monomer (EPDM) nanocomposites, prepared from organically modified montmorillonite (CMMT), is studied under accelerated UV irradiation (lambda >= 290 nm) for different time intervals. The development of functional groups during degradation is monitored by FT-IR spectroscopy whereas, surface changes are studied by scanning electron microscopy (SEM). The effect of clay modifier and clay concentration on the degradability are studied. The degradation of neat polymer and composites taking place traditionally and an increase in carbonyl and hydroxyl groups are observed with irradiation time. Neat EPDM is found to be less degradable than nanocomposites. Degradation products, as seen by FT-IR in nanocomposites are found to be the same as in neat polymer but are generated at a faster rate. According to the experimental results, one can define that both ammonium ion and neat montmorillonite (MMT) accelerate the photo-oxidation of EPDM.
Keywords: carbonyl index; Degradation; EPDM; layered silicates; Nanocomposites; photooxidation

Cross-linking assessment after accelerated ageing of ethylene propylene diene monomer rubber - Tomer, N. S.; Delor-Jestin, Florence; Singh, R. P.; Lacoste, Jacques (Polymer Degradation and Stability, 2007)
The ageing of filled and cross-linked ethylene propylene diene elastomer (EPDM) has been studied under accelerated UV irradiation (lambda >= 290 nm) at 60 degrees C, thermal ageing at 100 degrees C and in nitric acid vapours for different time intervals. Hardness measurements were performed. DSC-thermoporosimetry was used to estimate the mesh size distribution and cross-linking densities for each ageing. The development of functional groups was monitored by ATR spectroscopy. An increase in oxidation with exposure time after the different types of ageing was observed. The thermal stability of EPDM was assessed by TGA and evolved volatile gases were identified using FTIR spectroscopy. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ageing; EPDM; Oxidation; thermal analysis; thermoporosimetry

Photo-oxidation of EPDM/layered double hydroxides composites: influence of layered hydroxides and stabilizers - Kumar, B.; Rana, S.; Singh, R. P. (Express Polymer Letters, 2007)
The photo-oxidation of ethylene propylene diene monomer (EPDM)/layered double hydroxide (LDH) composites as well as EPDM/LDH with stabilizers is studied under accelerated UV irradiation (lambda >= 290 nm) at 60 degrees C for different time intervals. The development of functional groups during oxidation was monitored by FT-IR spectroscopy. The photo-degradation of the pristine polymer and composites take place and the increase in hydroxyl and carbonyl groups with irradiation times, was estimated. EPDM filled LDH showed higher degradation rate than pristine EPDM, while in acidic medium EPDM/LDH showed almost equal degradation as in isolated conditions. These results show the advantages of LDHs as a filler as well as an acid killer. The effect of stabilizers is very less because of their concentration in comparison of LDH.
Keywords: EPDM; layered double hydroxides; Photo-oxidation; polymer composites

Selective oxidation of anthracene using inorganic-organic hybrid materials based on molybdovanadophosphoric acids - Bordoloi, Ankur; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
{Inorganic-organic hybrid materials were synthesized by immobilization of molybdovanadophosphoric acids onto mesoporous silicas, such as MCM-41, MCM-48, and SBA-15, through an organic linker. 12-Molybdovanadophosphoric acids of the general formula H3+xPMO12-xVxO40 (x = 0-3).nH(2)O, such as H-4[
Keywords: EPDM; Photostabilization; polymeric HALS

Synthesis, characterization, and performance evaluation of polymeric hindered amine light stabilizers (HALS) in EPDM - Rana, Sravendra; Singh, Raj Pal (E-Polymers, 2007)
Polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the brominated ethylene-propylene-diene terpolymer (EPDM) was synthesized. The brominated EPDM was synthesized as an intermediate for the synthesis of a new polymeric hindered amine light stabilizer. The grafting and functionalization reactions were characterized by FTIR and (HNMR)-H-1 spectroscopy. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The results of the study give evidence for superiority of polymeric HALS over that of melt blended conventional HALS.
Keywords: EPDM; Photostabilization; polymeric HALS